2020
DOI: 10.1111/jfb.14372
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of Arapaima sp.: integrating stomach contents and local ecological knowledge

Abstract: The giant arapaima (Arapaima sp.) has been described as a fish of change in Amazonia because of its important role in the conservation of floodplains, food security and income generation for rural communities. Nonetheless, despite the cultural, ecological and economic importance of arapaima, data on diet are scarce. Aiming to expand knowledge about arapaima diet in western Amazonia, scientific knowledge was integrated with the knowledge of local dwellers. During the low-water period (September 2018) and the fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
2
0
0
Order By: Relevance
“…The sum may be greater than 100%, as fishers could cite more than one food item for each studied fish species. Those food interactions that agree with fish feeding relationships reported in the biological literature (Best, 1984;Silva et al, 2013;Dary et al, 2017;Jacobi et al, 2020) are marked in yellow.…”
Section: Discussionsupporting
confidence: 67%
“…The sum may be greater than 100%, as fishers could cite more than one food item for each studied fish species. Those food interactions that agree with fish feeding relationships reported in the biological literature (Best, 1984;Silva et al, 2013;Dary et al, 2017;Jacobi et al, 2020) are marked in yellow.…”
Section: Discussionsupporting
confidence: 67%
“…The generalist strategy found in the study corroborates with the reported in the literature for predatory fish (Cardoso et al, 2019;Jacobi et al, 2020;Mérona and Rankin-de-Mérona, 2004), since, in this seasonal phase, there is a greater supply of allochthonous items of animal and vegetable origin, such as winged insects, fruits and seeds that fall from the trees (Claro-Jr et al, 2004;Goulding, 1990) and serve as food for fish. This phase also aids the fish by allowing them to store fat until the low water period, when food becomes scarce.…”
Section: Discussionsupporting
confidence: 87%
“…They belong to a group of primitive bony fish known as bonytongue fish, because their tongues are used to crush prey against the roofs of their mouths. Smaller Arapaima are generalist feeders, consuming a variety of invertebrates, such as the Amazon River prawns, mayflies, and crickets, while larger Arapaima can consume larger prey, often catfish, cichlids, hatchetfish, and pacu (Watson et al 2013;Carvalho et al 2018;Jacobi et al 2020). During low water periods, many isolated lakes can become hypoxic (i.e., low in oxygen).…”
Section: Habits Habitat and Life History Of Arapaimamentioning
confidence: 99%